Aspidistra tenuifolia (Asparagaceae), a new species from China - Meng, Tao; Yang, Jin-Cai; Tang, Wen-Xui; Pan, Bo; Lin, Chun-Rui (Phytotaxa, 2014)
In the course of investigating limestone plants in south-western Guangxi, China in 2011, we discovered an unusual Aspidistra Ker Gawler (1822: without pagination) in Jinxi Xian, Guangxi, the leaf blade usually narrowly long to ribbon-shaped, its flower was dark purple, emitting unique flavor, the stamens were inserted on the bottom of perigone tube, closely attached to the pistil base. The plant was brought to the Guangxi Institute of Botany, Guilin. In the following year it flowered regularly, making possible a detailed description based on living plant material. Consultation of herbarium material and careful comparison with all Aspidistra species hitherto known from Guangxi Prov. and adjacent North Vietnam (Wan & Huang 1987, Liang & Tamura 2000, Li 2004, Tillich 2005, 2008, Tillich et al. 2007, Liu et al. 2011, He et al. 2011, Lin et al. 2010, 2012, Lin & Liu 2011, Averyanov & Tillich 2012, Tillich & Averyanov 2012), made clear that the plant is an new species, which we describe below.